Assessment of access to health care systems in Tanzania with emphasis on social health insurance and micro -insurance schemes - Themba, Ferdinand Marcel (Institute of Development and Labour Law, 2026)
Health care services in Tanzania vary according to geographical location and the provisioning of health services is relatively poor. This is true when one considers the fact that about 25 % of Tanzanians live below the poverty line. Other factors include the lack of human resources personnel and the problems in drugs supply. This study examines the efforts of the government on health care provision and administration since 1961. The study critically discusses the current health care services financing system by way of insurance both statutory and the micro insurance schemes. The study reveals that the government allowed private health care services which have a good partnership with public sector in the provision of health care services. Besides, in 2002 the government allowed traditional and alternative health practices. Also, the study describes the effectiveness of health sector reforms which led to the decentralisation of the provision of health services to the local government and the adoption of primary health care services which focused on the improvement of health care services in the village and ward level. The government introduces alternative means of financing health care services after it became impossible to provide free health care services. On this footing the study examines the challenges and effectiveness of the National Health Insurance Fund (NHIF) which provides health care insurance to public service employees. In addition, the Social Health Insurance Benefits offered by the National Social Security Fund (NSSF), Community Health Fund (CHF), Community Based Health Financing (CBHF) and private insurance are examined on the basis of their achievement and challenges in financing health care services. Initiatives of providing health care assistance for the identified groups of people as per the National Health Policy 2007 attract attention of the researcher. The study makes a number of recommendations including the need to amend the Constitution to provide for right to health. Also the study recommends on the need to increase the public budget on health services which would solve the problem of inequalities of health care facilities in some districts and sponsor education to medical personnel. The study further recommends on the improvement on drugs supply and legal control of private health providers. The fact that the provisioning of health care services has taken the dimension of health care financing by way of either statutory insurance or micro insurance schemes the study recommends on the need to increase the coverage of health insurance schemes and further that the government need to address the issue of regulation of private health insurance schemes. On the part of micro insurance schemes there is need to adopt the means of collaboration as between the informal health insurance schemes and formal health insurance schemes so as to attain solidarity.